Comparative Analysis of the Capacity of Elite Suppressor CD4(+) and CD8(+) T Cells To Inhibit HIV-1 Replication in Monocyte-Derived Macrophages - Walker-Sperling, Victoria E. K. (American Society for Microbiology, 2014)
Elite controllers or suppressors (ESs) are HIV-1-infected individuals who are able to maintain viral loads below the limit of detection of clinical assays without antiretroviral therapy. The mechanisms of virologic control are not fully understood, but ESs have been shown to have a more effective CD8(+) T cell response to infected CD4(+) T cells than chronic progressors (CPs). While macrophages are another cell type productively infected by HIV-1, few studies have examined the ability of primary effector T cells to suppress HIV-1 replication in these target cells. Here, we compared the ability of unstimulated primary CD4(+) and CD8(+) effector T cells to suppress viral replication in monocyte-derived macrophages (MDMs) in ESs and CPs. While CD4(+) effector T cells were capable of inhibiting viral replication in MDMs, the magnitude of this response was not significantly different between ESs and CPs. In contrast, the CD8(+) T cells from ESs were significantly more effective than those from CPs at inhibiting viral replication in MDMs. The CD4(+) T cell response was partially mediated by soluble factors, while the CD8(+) T cell response required cell-to-cell interaction. Our results suggest that the individual contributions of various effector cells should be considered in rational vaccine design and in ongoing eradication efforts. IMPORTANCE Elite suppressors are individuals capable of maintaining low-level viremia in HIV-1 infection without antiretroviral drugs. Their T cell responses have been implicated in eliminating infected CD4(+) T cells, and as such, elite suppressors may represent a model of a functional cure of HIV-1 infection. Here, we sought to determine whether the suppressive T cell responses against infected CD4(+) T cells also apply to infected macrophages by comparing the responses of elite suppressors and HIV-1-positive individuals on highly active antiretroviral therapy (HAART). Our results show that the CD8(+) cells but not CD4(+) T cells from elite suppressors have a response against infected macrophages superior to the response of CD8(+) cells from patients on HAART. Our results suggest that the induction of a CD8(+) T cell response effective against infected macrophages is an outcome to consider in rational vaccine design.